Nicotinamide Phosphoribosyltransferase in Smooth Muscle Cells Maintains Genome Integrity, Resists Aortic Medial Degeneration, and Is Suppressed in Human Thoracic Aortic Aneurysm Disease. Issue 12 (9th June 2017) - Watson, Alanna; Nong, Zengxuan; Yin, Hao; O'Neil, Caroline; Fox, Stephanie; Balint, Brittany; Guo, Linrui; Leo, Oberdan; Chu, Michael W.A.; Gros, Robert; Pickering, J. Geoffrey
Abstract : Rationale: : The thoracic aortic wall can degenerate over time with catastrophic consequences. Vascular smooth muscle cells (SMCs) can resist and repair artery damage, but their capacities decline with age and stress. Recently, cellular production of nicotinamide adenine dinucleotide (NAD + ) via nicotinamide phosphoribosyltransferase (Nampt) has emerged as a mediator of cell vitality. However, a role for Nampt in aortic SMCs in vivo is unknown. Objectives: : To determine whether a Nampt-NAD + control system exists within the aortic media and is required for aortic health. Methods and Results: : Ascending aortas from patients with dilated aortopathy were immunostained for NAMPT, revealing an inverse relationship between SMC NAMPT content and aortic diameter. To determine whether a Nampt-NAD + control system in SMCs impacts aortic integrity, mice with Nampt -deficient SMCs were generated. SMC- Nampt knockout mice were viable but with mildly dilated aortas that had a 43% reduction in NAD + in the media. Infusion of angiotensin II led to aortic medial hemorrhage and dissection. SMCs were not apoptotic but displayed senescence associated-ß-galactosidase activity and upregulated p16, indicating premature senescence. Furthermore, there was evidence for oxidized DNA lesions, double-strand DNA strand breaks, and pronounced susceptibility to single-strand breakage. This was linked to suppressed poly(ADP-ribose) polymerase-1 activity and was reversible on resupplying NAD + with nicotinamide riboside. Remarkably, we discovered unrepaired DNA strand breaks in SMCs within the human ascending aorta, which were specifically enriched in SMCs with low NAMPT. NAMPT promoter analysis revealed CpG hypermethylation within the dilated human thoracic aorta and in SMCs cultured from these tissues, which inversely correlated with NAMPT expression. Conclusions: : The aortic media depends on an intrinsic NAD + fueling system to protect against DNA damage and premature SMC senescence, with relevance to human thoracic aortopathy. Abstract : Supplemental Digital Content is available in the text.